Kala Malam Bulan Mengambang - 'Noir' parody with a satirical edge? / Norman Yusoff - Yusoff, Norman (UPENA, 2008)
Mamat Khalid's Kala Malam Bulan Mengambang (2008), which focuses upon an intriguing story of an investigative journalist having to confront mysterious disappearances, conspiracies and ghostly presence is a rambunctious black-and-white send-up of (Hollywood) film noir. The film is a strikingly self-reflexive display of generic possibilities as cultural performance, for it flaunts an intertextual style, consciously showcasing its production process, and constantly 'quotes' from other cultural texts. This essay argues that Kala Malam Bulan Mengambang works as both a parody and a satire. As a parody, the film's target is concerned with formal and aesthetic elements. Mamat deftly interweaves a melange of film genres, ranging from Hollywood noir to old Malay horror. As a satire, the film is comedy with an edge, with its target being social and political in some way. Within its narrative, the film pokes fun at contemporary Malaysian society and politics in a subtle, underlying manner, thus providing the viewer with a fascinating subtext. By exploring the film's generic discursivities in terms of Mamat's parodic strategy and satirical mode, the ultimate aim of this essay is to sanction a more appropriate generic label for the film.